A Comparative Study of Indonesian and South Korean Anticorruption Education Curricula - Zulaiha, Aida Ratna; Johan, Riche Cynthia (Lembaran Ilmu Kependidikan, 2025)
Anti-corruption education (ACC) has become an important part of the national education system in both Indonesia and South Korea, with the aim of building a generation with morality and integrity. This study aims to compare the PAK curriculum integrated in moral or character education in the two countries, by examining the education system, cultural background, values promoted, curriculum, learning methods, and pedagogical innovations that contribute to the integrity of students. This research uses a qualitative approach with a literature-based comparative study method, analyzing official government documents, academic journals and previous research. The analysis method refers to the Comparative Education Research Center (CERC) framework which includes education system, culture, values, curriculum and pedagogical innovation. The results show that moral education in South Korea has been a mandatory part since 1973, with the integration of anti-corruption values supported by the Anti-Corruption and Civil Rights Commission (ACRC). Meanwhile, in Indonesia, character education based on Pancasila values has been implemented since the beginning of independence and developed until the Independent Curriculum era with the support of the Corruption Eradication Commission (KPK). Both countries use a project-based approach and intersectoral collaboration in the implementation of PAK, with pedagogical innovations tailored to the local context. Integrating anti-corruption values into the education system has proven to be an effective strategy in building a generation with integrity.